The Human Existential Crisis from Seyyed Hossein Nasr's Perspective - Munawar, Muhamad Aris (TAJDID, 2020)
This page seeks to further explain Seyyed Hossein Nasr's idea of thought, one of the Muslim intellectuals who had a significant impact on Persian thought. This study employs a method called literature analysis, in which the author not only reads the pertinent literature but also critically and in-depth assesses the pertinent prior research literature. The results showed that Sayyed Hossein Nasr gave the view that existential or spiritual crises experienced by humans stem from modern human rebellion against God. That is when humans leave God in order to confirm their existence.